The Pragmatic Binding Power of DSN-MUI Fatwas Within Modern Financial Institutions - I Gede Arya Budi Dwyartha; Wafda Vivid Izziyana; Popova Sonia (Socio Legal and Islamic Law, 2025)
The ambiguous transformation of National Sharia Council–Indonesian Ulema Council (DSN-MUI) fatwas into positive law creates a critical legal loophole and compliance vulnerability in the operational governance of Indonesian Islamic financial institutions. This study aims to analyze the legal binding authority of DSN-MUI fatwas and evaluate their practical enforcement within Islamic financial institution operations. This study employs a normative legal research method. The results demonstrate that while DSN-MUI fatwas hold strong moral and religious legitimacy, they lack direct state-enforceable executive power unless explicitly codified into binding banking or financial services regulations. This structural gap leads to inconsistent implementation across different institutions, where fatwa compliance varies significantly depending on internal corporate willingness and local Sharia supervisory board oversight. Furthermore, the absence of standardized statutory sanctions for fatwa non-compliance weakens institutional accountability and leaves consumers exposed to financial-sharia risks. The findings indicate that the current self-regulatory approach fails to guarantee uniform Sharia compliance, as institutions frequently prioritize commercial viability over strict fatwa adherence due to weak external regulatory pressure. Consequently, the operational binding force of these fatwas remains highly pragmatic rather than legally absolute. This study concludes that formalizing fatwas directly into state-backed financial regulations and establishing rigorous statutory enforcement mechanisms are imperative to eliminate legal uncertainty, strengthen institutional accountability, and guarantee robust consumer protection within the national Islamic financial system.